FDI dan Emisi CO₂: Apakah Ada Hubungan Kausal di ASEAN? Studi Kasus Indonesia, Malaysia, dan Singapura - Muhammad Esa Febriyanto; Niniek Imaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Economic growth is the main indicator for a country's economic health, where Foreign Direct Investment (FDI) plays an important role in boosting economic growth. ASEAN member countries, including Indonesia, Singapore, and Malaysia, have introduced various policies to facilitate FDI to encourage economic growth. This study aims to analyze the causal relationship between Foreign Direct Investment (FDI) and CO2 emissions in ASEAN, and vice versa, namely the relationship between CO2 emissions and FDI. The study was conducted in three ASEAN countries (Indonesia, Singapore, and Malaysia) with an analysis period from 1990 to 2022. The method used in this study is Vector Autoregression (VAR) followed by the Vector Error Correction Model (VECM). The results show that based on the Granger Causality Test, no causal relationship between FDI and CO2 emissions was found in the three countries studied. However, based on VECM analysis, it was found that the CO2 variable has an influence on FDI in Indonesia, Singapore, and Malaysia.